Sexual harassment in organizational culture: a transformative approach - Dougherty, Debbie S. (Cognella, 2023)
"Sexual Harassment in Organizational Culture: A Transformative Approach is centered on a long running problem that has vexed organizations across time: Why can't we prevent sexual harassment that has damaged individuals, organizational teams, organizations, and their larger consituents? In an effort to create the type of change necessary to prevent such harassment, author Debbie S. Dougherty not only describes what sexual harassment is, but also walks readers through a model of organizational culture to highlight how sexual harassment is woven into organizational culture through communication. This transformational model focuses on how organizational cultures are created and how those cultures can evolve through careful and thoughtful communication. The book presents organizational problems and then provides theories, research, and application to better understand each problem. Readers learn about theoretical approaches to organizational communication, how to identify hidden problems in organizational culture, strategies for the transformation of culture, and more. Sexual Harassment in Organizational Culture is written for current and aspiring change agents who are serious about addressing sexual harassment. It is an exceptional book for courses and practitioners in the ares of organizational communication, behavior management, and human resources"--Back cover